γ-Aminobutyric acid treatment induced chilling tolerance in postharvest peach fruit by upregulating ascorbic acid and glutathione contents at the molecular level - Zhou, Chujiang; Dong, Wanqi; Jin, Shuwan; Liu, Qingli; Shi, Liyu; Cao, Shifeng; Li, Saisai; Chen, Wei; Yang, Zhenfeng (Frontiers in Plant Science, 2022)
Peach fruit was treated with 5 mM γ-aminobutyric acid (GABA) to further investigate the mechanism by which GABA induced chilling tolerance. Here, we found that GABA not only inhibited the occurrence of chilling injury in peach fruit during cold storage but also maintained fruit quality. Most of the ascorbic acid (AsA) and glutathione (GSH) biosynthetic genes were up-regulated by GABA treatment, and their levels were increased accordingly, thus reducing chilling damage in treated peaches. Meanwhile, the increased transcript of genes in the AsA-GSH cycle by GABA treatment was also related to the induced tolerance against chilling. GABA treatment also increased the expression levels of several candidate ERF transcription factors involved in AsA and GSH biosynthesis. In conclusion, our study found that GABA reduced chilling injury in peach fruit during cold storage due to the higher AsA and GSH contents by positively regulating their modifying genes and candidate transcription factors.